Evaluation of seed components of wild soybean (Glycine soja) collected in Japan using near-infrared reflectance spectroscopy. Issue 2 (23rd January 2017) - Wee, Chi-Do; Hashiguchi, Masatsugu; Ishigaki, Genki; Muguerza, Melody; Oba, Chika; Abe, Jun; Harada, Kyuya; Akashi, Ryo
Abstract: Seed composition, including the protein, lipid and sucrose contents of 334 accessions of wild soybean ( Glycine soja ) collected in Japan, was evaluated using near-infrared reflectance spectroscopy (NIRS) technology. The distribution of protein, lipid and sucrose contents and correlations among these three classes of seed components were determined. Protein, lipid and sucrose levels ranged in accessions from 48.6 to 57.0, 9.0 to 14.3 and 1.24 to 3.53%, respectively. Average levels of protein, lipid and sucrose in the accessions were 54, 11 and 2.5%, respectively. High negative correlations were observed between the protein and lipid contents, and the protein and sucrose contents. Mean levels of the three constituents were compared among collection sites classified by climatic conditions. The total protein content of accessions from regions with a high annual mean temperature was high. The protein content of accessions from the II-1 region was higher than those from the III-3 region, and the sucrose content from the II-1 region was lower than those from regions III-2 and IV-3. The lipid content of plants from the II-1 region was lower than those from other regions, and the accessions in region II had a higher protein content and lower sucrose and lipid contents than the other regions. These results provide diverse and wide-ranged protein, lipid and sucrose contents information of Japanese wild soybean resources according to climatic region; thus, providing a foundation for the future development and selection of new soybean varieties with desired traits in global environmental changes.